PERAN LEMBAGA AMIL ZAKAT TERHADAP USAHA MIKRO YANG TERDAMPAK COVID-19 DI KOTA PONTIANAK - Diah Arminingsih; Sri Rejeki Adiyanti (Tarbawi Khatulistiwa, 2021)
MSMEs (Micro, Small and Medium Enterprises) are the backbone that supports the Indonesian National economy. MSMEs contribute 60% of GDP and absorb labor up to 97%. However, with the covid-19 outbreak, there were 67,051 MSME players and the most affected was 35.88% of the business to provide food and beverage accommodation. In this case, the empowerment of micro businesses LAZ (Lembaga Amil Zakat) has an important role to play in developing and helping micro businesses affected by Covid-19. So a study is needed related to the role of LAZ in Pontianak city in the field of providing food and beverage / culinary accommodation that is affected by Covid-19. The purpose of this study was to determine the role of LAZ in micro businesses affected by Covid-19 in the city of Pontianak. This type of qualitative research uses the data analysis method of Miles and Huberman. Data collection techniques through observation, interviews, and documentation. The research was conducted at the Zakat House and Ummat Wallets, as well as 7 mustahik micro business actors providing food and beverage / culinary originating from one of these LAZs. Based on the research results, it shows that the zakat fund collection system at the Zakat House and Ummah Wallets is carried out optimally through various means and media that are easily accessible to the public so that funds are easily collected. Zakat funds are distributed on target according to 8 asnaf, and management and assistance are still carried out. Keywords: MSMEs; Lembaga Amil Zakat;  Pandemic Covid-19